Amniotic Fluid Glucose Concentration: A Marker for Infection in Preterm Labor and Preterm Premature Rupture of Membranes - Gary A. Dildy; Mark D. Pearlman; Leon G. Smith; Guillermo Tortolero-Luna; Sebastian Faro; David B. Cotton (Hindawi Limited, 1994)
Amniotic fluid Gram stain and culture have been utilized as laboratory tests of microbial invasion of the amniotic cavity. The Gram stain of amniotic fluid has a low sensitivity in the detection of clinical infection or microbial invasion of the amniotic cavity, and amniotic fluid culture results are not immediately available for management decisions. Glucose concentration is used to diagnose infection in other sites such as cerebrospinal fluid.